Visual loss in patients with sphenoethmoidal cells. Issue 2 (19th February 2015) - Rimmer, J; Beale, T; Lund, V J
Abstract: Background: A sphenoethmoidal cell is a posterior ethmoid cell that pneumatises superiorly and/or laterally to the sphenoid sinus. Disease within such a cell may cause visual symptoms because of the close relationship of the optic nerve. Case reports: This paper reports four cases of chronic rhinosinusitis involving a sphenoethmoidal cell, two with visual loss. The management of such cases is discussed and the current literature is reviewed. Conclusion: Pathology within a sphenoethmoidal cell must be considered in cases of optic neuropathy. The presence of these cells may be relevant even in cases of seemingly uncomplicated rhinosinusitis as they are associated with a higher rate of optic nerve protrusion and dehiscence.